Diksi dan Tema dalam Lagu Deny Caknan: Kartonyono Medot Janji dan Satru - Putri, Shilfia Amalia (Program Studi Pendidikan Bahasa dan Sastra Daerah, 2024)
This study aims to analyze the use of diction and themes contained in Denny Caknan's Dangdut Song Lyrics. The method used is a qualitative descriptive method because the object is the text of the Song Lyrics. The research data is based on Kertonyono Medhot Janji and Satru song lyrics taken from the YouTube platform. Data analysis uses content analysis by comparing data with theories about stylistics, especially those related to diction. The results showed the presence of denotative, connotative, and polysemy diction in the two songs used as data.